Studies of Gold Adsorption from Chloride Media - AKTAŞ, SERDAR (UNIV FED SAO CARLOS, DEPT ENGENHARIA MATERIALS, 2015)
In this paper, adsorption of gold from chloride media using commercial sorbent (Lewatit TP 214 (L-214)) and biomass residue (rice hull (RH)) were investigated. The different adsorption parameters, sorbent dosage, contact time, temperature and pH of solution on adsorption (%) were studied in detail on a batch sorption. Before the RH was activated, adsorption (%) was poor compared with L-214. However, after the RH was activated at 1000 degrees C under an argon atmosphere, the gold adsorption (%) increased four-fold. X-ray fluorescence (XRF) was used to explore the feasibility this material as an adsorbent for the removal of gold from aqueous solutions. The adsorption equilibrium data were best fitted with the Langmuir isotherm model. The maximum adsorption capacities, Q(max), at 25 degrees C were found to be 93.46 and 108.70 mg/g for the activated rice hull (ARH) and L-214, respectively. Thermodynamic calculations using Delta H degrees, Delta S degrees, Delta G degrees and E-a values indicate that the adsorption process was spontaneous and endothermic.
Keywords: adsorption; activated carbon; chloride solution; waste recovery; RICE HUSK ASH; AQUEOUS-SOLUTIONS; GOLD(III); EXTRACTION; BIOSORPTION; KINETICS; CARBON